2004
DOI: 10.1103/physrevlett.92.097205
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Quasiparticle Renormalization on the Spin Wave Energy Scale

Abstract: High-resolution photoemission data of the (110) iron surface reveal the existence of well-defined metallic surface resonances in good correspondence to band calculations. Close to the Fermi level, their dispersion and momentum broadening display anomalies characteristic of quasiparticle renormalization due to coupling to bosonic excitations. Its energy scale exceeds that of phonons by far, and is in striking coincidence with that of the spin wave spectrum in iron. The self-energy behavior thus gives spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 25 publications
5
76
0
Order By: Relevance
“…This energy range is quite different from that discussed in recent high-resolution ARPES studies on Fe or Ni. 28,30,71 There, the very low BE range E B 300 meV has been treated, in which a renormalization of the charge carrier dynamics by a coupling to phonon or magnetic excitations is important. All the observed peaks in Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This energy range is quite different from that discussed in recent high-resolution ARPES studies on Fe or Ni. 28,30,71 There, the very low BE range E B 300 meV has been treated, in which a renormalization of the charge carrier dynamics by a coupling to phonon or magnetic excitations is important. All the observed peaks in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 It has been shown that very close to the Fermi energy mass renormalizations are even higher, reaching values up to 3.6. [28][29][30] Moreover a strong broadening of the ARPES peaks in Fe has been observed amounting to about 60% of the BE. 27 Most recently, we have published a detailed comparison of SARPES measurements and DMFT/3BS calculations on Fe indicating that the present state-of-the art many-body calculations still underestimate correlation effects.…”
Section: Introductionmentioning
confidence: 99%
“…Such kinks are primarily caused by electron-boson interactions and many cases of electron-phonon [1][2][3] or electron-magnon [4] induced kinks have been reported. In the cuprate hightemperature superconductors, strong kinks have been found near the Fermi energy [5,6], and their origin as well as their significance for the mechanism for hightemperature superconductivity have given reason to some debate [7].…”
mentioning
confidence: 99%
“…[50] In studies of the Fe(001) surface Schafer et al identified a mass renormalization up to a binding energy of 120 meV. The latter energy was too large to be associated with phonons (Debye energy, θ D ∼ 39 meV) and thus the authors identified the self-energy corrections with scattering from spin excitations.…”
Section: Magnetic Systemsmentioning
confidence: 99%
“…Such effects have been found in photoemission studies of gadolinium [48] [49] and of iron. [50] The spin dependent electronic structure of these materials has been studied with spin-resolved photoemission. [51] However there has only been one such study with sufficiently high energy resolution to examine in detail the spin resolved self-energy effects.…”
Section: Magnetic Systemsmentioning
confidence: 99%